Accent bias and fair access in Britain 2017-2020 - Levon, Erez (UK Data Service, 2020)
The accent bias project examines attitudes to major accents in England, changing attitudes across age groups, attitudes to new urban dialects, and explores how accent interferes with assessments of professional ability. Using a combination of insights from sociolinguistics, social psychology, and labour market economics, we explore accent bias in relation to a number of social and linguistic factors. The first component of our study examines current attitudes to accents in the UK amongst the British public. The second component of our study explores the effects of accent bias in professional contexts. We explore a number of different social and linguistic factors to assess whether accent bias plays a role in objective assessments of professional competence and ability. Fair access to employment is the cornerstone of a just, equal and socially mobile society. Despite efforts in recent years by government and industry to implement fair access policies, a 2015 report by the government's Social Mobility Commission revealed persistent bias in recruitment and selection processes in elite sectors of the UK economy in favour of applicants from middle-class backgrounds. This bias, which Commission Chair Alan Milburn describes as keeping working-class candidates "locked out of top jobs" results in part from the reliance on subjective and non-educationally-based "talent" criteria, such as a candidate's appearance and communication style, when making hiring decisions. Characterised by the report as "poshness", talent criteria such as these privilege middle-class norms and behaviours, such as accent, at the expense of an objective assessment of a candidate's aptitude, and can ultimately impede social mobility. This project examines the role of accent bias in hiring situations in the legal profession, a sector identified by the Commission report as particularly prone to the use of subjective criteria. Specifically, we investigate whether bias against certain regional and class-linked accents in the UK interferes with employers' objective assessment of a candidate's job suitability. We also investigate sources of bias and test whether different anti-bias interventions are effective. For scholars in linguistics, social psychology and related fields, the project offers an updated quantitative examination of attitudes to accent variation in Britain, and a novel understanding of the real-world effects of accent bias. For legal, HR, and policy stakeholders, the project responds to a key recommendation of the Commission's report about the need to "interrogate current definitions of talent to ensure that applicants are not ruled out for reasons of background rather than aptitude and skill" and provides concrete evidence on the efficacy of different types of interventions. The project makes use of survey and experimental methods to examine the effect of accent bias on hiring decisions in law firms. Five accents that differ in terms of region and class will be examined: two Northern (Leeds, General Northern), two Southern (Estuary, Multicultural London), and the nationwide standard (Received Pronunciation).